ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA ANGGOTA KELOMPOK USAHA KECIL DAN MIKRO (UKM) BINAAN UP3HP DI KOTA BENGKULU - Gunawan, Romi (Universitas Dehasen Bengkulu, 2015)
Romi Gunawan; The research purpose to observe the performance of SME and to analyze the influence of capital, age`s respondent, the age of SME and education toward omzet of UP3HP member in Bengkulu City. The analysis instrumen used is multiple liniear reggresion on the covident level of 95%. From the researce know that omzet of the SME nurture by UP3HP stil in small clasification. there are some enterpreneur who have old enter prises common have small omzet. And than, capital, age`s respondent, the age of SME and education have significance`s influence toward omzet. Extended of influence mentioned point out of determination coeffisient (R2) amount of 80%.Key words: Performance of SME, Omzet.